Estimasi Posisi Objek dalam Gedung Berdasarkan GSM Fingerprint - Hani Rubiani; Widyawan; Lukito Edi Nugroho (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
Most research of indoor localization is based on the use of short-range signals, e.g. WiFi, Bluetooth, ultra sound, and infrared. This research discusses indoor localization using the Global System for Mobile Communication (GSM). The GSM has many advantages that is explained as follows. The system can be used in vast area coverage and worked even the electrical condition of the building is being extinguished. The estimation of object position uses Receive Signal Strength (RSS) GSM fingerprinting. The experiment is conducted with 2, 3, and 4 cell-ID. The localization phase uses Naive Bayes (NB) method. Afterwards, the results will be compared with Nearest Neighbour (NN) method. The results show a correlation between the number of cell ID with average minimum distance error. The accuracy is 7.89 m using NB with four cell ID. The error is better than the use of k-NN method which has accuracy of 12.19. For the all scenario, NB method has better accuracy than k-NN method.